Analisis Sistem Informasi Akuntansi Persediaan Barang Dagang Untuk Meningkatkan Efektivitas Pengendalian Internal Pada PT. Lotte Mart Surabaya - Ratih Dwitama Wardani; Heri Toni; Sutini Sutini; Diana Zuhro; Tjandra Wasesa; Wiratna Wiratna (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This increasingly fierce competition requires companies to manage all their resources as optimally as possible so that companies can produce and offer products that are needed and desired by consumers with high quality at adequate prices to continue to survive and can continue to develop so that they can generate profits. Business. Merchandise inventory is very important for trading companies. Inventories at trading companies generally consist of various types of trading goods in relatively large quantities. A diverse inventory of merchandise is one of the characteristics of a distributor’s business. Distributors whose merchandise are the object of research are a form of business that contributes to meeting the basic needs of Indonesian society. Inventory that is susceptible to various types of damage, obsolescence, excess or shortage of inventory. Inventory management activities include good and accurate recording according to needs as well as directing the flow and handling of inventory appropriately from procurement, storage to release. Supplies must be available when needed, with adequate quality and quantity, at the right place and at a reasonable price. Ignoring any responsibility related to inventory will have a negative impact on the smooth operation of traders. Inventory is needed to create sales to generate profits. Inventory is a current asset that has quite a high risk in the company’s activities. The risk from a physical perspective is if there is fraud in the inventory in the warehouse due to lack of supervision and damage to goods occurs which results in disappointed consumers.